2010
DOI: 10.1086/655226
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Immune Response to 2009 Influenza A(H1N1) Vaccines in Adults: A Randomized, Double‐Blind, Controlled Trial

Abstract: A double-blind, randomized, controlled trial involving 706 adults was conducted to evaluate the immunogenicity and safety of different dosages of whole-virion or split-virion H1N1 influenza vaccines with or without aluminum adjuvant. A rapid and strong immune response was induced at day 14 after the first injection. The seroprotection rates ranged from 72.7% (95% confidence interval [CI], 62.7%-81.1%) for 5-microg whole-virion aluminum formulation to 97.0% (95% CI, 90.9%-99.7%) for 30-microg split-virion nonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 8 publications
(13 reference statements)
1
29
0
Order By: Relevance
“…In a previous analysis we found that two years after the emergence of the influenza 2009 H1N1 pandemic less than 30% of the 73 registered randomized trials on the potential vaccines had been published, representing 38% of the randomized sample size. 7 The present update showed a relevant improvement, as four years after trial completion the results of approximately 80% of the randomized participants had been published (90% including results in ClinicalTrials.gov). However, data published more than four years (or even one year) after a pandemic (and vaccine distribution) are already of little or no value.…”
Section: Comparison With Other Studiesmentioning
confidence: 63%
See 2 more Smart Citations
“…In a previous analysis we found that two years after the emergence of the influenza 2009 H1N1 pandemic less than 30% of the 73 registered randomized trials on the potential vaccines had been published, representing 38% of the randomized sample size. 7 The present update showed a relevant improvement, as four years after trial completion the results of approximately 80% of the randomized participants had been published (90% including results in ClinicalTrials.gov). However, data published more than four years (or even one year) after a pandemic (and vaccine distribution) are already of little or no value.…”
Section: Comparison With Other Studiesmentioning
confidence: 63%
“…2 31 Also, there is a substantial literature in various specialties that trials with non-significant, less favorable, or even "negative" results are more likely to be unpublished or published late compared with significant trials or trials with results that are in line with investigators' hypotheses. 7 14 16 17 19 21 23 32-37 Furthermore, half of the 16 studies on the topic documented a lower likelihood of publication for the trials sponsored by industry. 10 23 36 38-41 Vaccine trials are largely dominated by industry sponsorship.…”
Section: Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other trials have reported a low incidence of adverse effects (0%-3%) and no significant difference in serious adverse events between influenza vaccine and placebo. [15][16][17] Of the RCTs, FLUCAD 31 was likely the most well designed. The authors attempted to minimize bias and confounding through appropriate randomization, use of intention-to-treat analyses, and minimal loss to follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…14 However, in prospective randomized trials that included CV outcomes for safety assessment, influenza vaccination was not associated with a reduction in CV events, [15][16][17][18] although these trials were limited by low event rates and potential for misclassification. 19 Both the American Heart Association/American College of Cardiology and the European Society of Cardiology recommend the influenza vaccine annually for individuals with established CVD [20][21][22] without specifically stating that the purpose is to reduce the risk of CV events.…”
Section: Introductionmentioning
confidence: 99%